2020
DOI: 10.1634/theoncologist.2019-0691
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Health Resource Use Among Patients with Metastatic Gastroenteropancreatic Neuroendocrine Tumors Treated at a Tertiary Referral Center

Abstract: Background. Although an increasing number of treatments have become available for patients with advanced gastroenteropancreatic neuroendocrine tumors (GEP-NETs), there remains little consensus on treatment sequence and its impact on health care resource use (HRU). We sought to describe treatment patterns and HRU, in a cohort of patients with metastatic GEP-NETs treated at a tertiary referral center in the U.S. Materials and Methods. We identified patients with a welldifferentiated, metastatic GEP-NET evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In 2020, a real-world study conducted at the Dana-Farber Cancer Institute, included 682 patients with well-differentiated metastatic GEP-NETs. [14,18] It was found that the SSA monotherapy was the most commonly chosen first-line regimen in metastatic GEP-NETs (69.7%). Besides, under the first-line setting, in 13.4% of the patients, SSAs were combined with other treatments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, a real-world study conducted at the Dana-Farber Cancer Institute, included 682 patients with well-differentiated metastatic GEP-NETs. [14,18] It was found that the SSA monotherapy was the most commonly chosen first-line regimen in metastatic GEP-NETs (69.7%). Besides, under the first-line setting, in 13.4% of the patients, SSAs were combined with other treatments.…”
Section: Methodsmentioning
confidence: 99%
“…A real-world study showed that SSA-based combination therapy was the most common second-line option for GEP-NETs. [14,17] As for the second-line therapies used in this study, 77.9% of the pNETs patients, 96.6% of the midgut NETs patients, and 78.7% of the patients with other primary locations were given SSA-based combination therapy. In these treatments, the drugs used concomitantly with SSAs included cytotoxic agents, everolimus, interferon, and investigational drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Of 26 patients in our study undergoing primary medical therapy, 12 received second-line systemic therapy, while 5 underwent salvage therapy. Others have reported 55% second-line therapy and 31% third-line therapy in patients with metastatic GEP-NET [20].…”
Section: Who Classification 2017mentioning
confidence: 99%
“…In pre-pandemic studies, patients with NETs averaged 25.7 outpatient visits and 5.6 inpatient visits annually, with the most common being visits to oncologist offices. 18,53 In response to governmental regulations and individual health concerns, oncology patient visits dropped dramatically in 2020 and, despite the lifting of stay-at-home orders, oncology service utilization continues to lag behind 2019 levels. 54 In an observational multi-center study, up to 40% of patients interrupted their therapy over the past year, due in part to the pandemic's impact on in-office visits.…”
Section: Octreotide Ir Use During Covid-19mentioning
confidence: 99%
“…Treatment of NETs is a health resource‐heavy process. In prepandemic studies, patients with NETs averaged 25.7 outpatient visits and 5.6 inpatient visits annually, with the most common being visits to oncologist offices [ 18 , 53 ].…”
Section: Octreotide Ir Use During Covid‐19mentioning
confidence: 99%